Pengaruh Komposisi Media Semai Sistem Tertutup Terhadap Perkecambahan Padi (Oryza Sativa L.) Inpari 32 - Harun, M Umar; Agustina, Heni; Bela, Triwulan Maryanita; Sopiana, Rina (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2023)
One of the efforts to facilitate the way of taking rice seeds from the nursery media is to use plastic sacks instead of directly from the soil. To obtain the best planting media, experiments have been carried out on the no tidal swamp Rice Fields, Pemulutan Village (3°05'42.7